Increased impulsivity as a vulnerability marker for bipolar disorder: evidence from self-report and experimental measures in two high-risk populations - Wessa, Michèle; Kollmann, Bianca; Linke, Julia; Schönfelder, Sandra; Kanske, Philipp (Journal of affective disorders, 2015)
Background - Heightened impulsivity has been suggested as a possible risk factor for bipolar disorder (BD). However, studies on high-risk populations are scarce and have mainly focused on individuals with a genetic risk. The present study investigated two high-risk samples for BD with regard to several aspects of the impulsivity construct. - Methods - Unaffected relatives of BD patients (genetically defined high-risk group, N=29) and participants scoring high on the Hypomanic Personality Scale (psychometrically defined high-risk sample, N=25) were being compared to respective control groups (N=27 and N=25) using a multi-method approach. Participants were accessed on the Barratt Impulsiveness Scale-11 (BIS-11, trait impulsivity), the Stop Signal Task (response inhibition), and the Cambridge Gambling Task (impulsive behavior in decision-making processes). - Results - Both high-risk groups reported heightened impulsivity on the BIS-11, as well as impulsive decision-making, whereas no significant group differences in response inhibition were observed. - Limitations - Limitations were the lack in specificity of the results for BD and the cross-sectional study design, which does not allow conclusions about the influence of impulsivity on the development of or resilience for BD in risk groups. - Conclusions - Our findings support the assumption that increased trait impulsivity and impulsive decision-making are a vulnerability marker for and an endophenotype of BD.
Gesehen am 30.06.2020